Clinical, biochemical, and radiographic effects of aminohydroxypropylidene bisphosphonate treatment in rheumatoid arthritis. Issue 5 (May 1989) - Ralston, S H; Hacking, L; Willocks, L; Bruce, F; Pitkeathly, D A
Abstract : A placebo controlled, double blind study of aminohydroxypropylidene bisphosphonate (APD), given by monthly intravenous infusion, was conducted in 40 patients with rheumatoid arthritis. Biochemical markers of increased bone resorption, such as fasting urinary calcium/creatinine ratio and hydroxyproline/creatinine ratio, were suppressed significantly in the APD group to approximately 50% and 60% of the pretreatment level respectively, and serum calcium fell transiently after the first APD infusion. There was no significant effect on disease activity in either the APD or placebo groups as judged by clinical (grip strength, morning stiffness, visual analogue score) or laboratory (haemoglobin, platelet count, erythrocyte sedimentation rate, C reactive protein) criteria. An exception was the articular index which improved to a similar degree in both groups, falling from (mean (SEM] 13.8 (1.8) to 7.2 (2.2) in the APD group and from 13.7 (1.9) to 6.8 (1.5) in the placebo group. Radiological progression occurred to a similar degree in both groups as assessed by the Sharp index (mean (SEM) 86 (13.1) v 95 (12.9)-APD group; 103 (15.1) v 110 (15.8)-placebo group), but there was no significant change in the Larsen index in either group (mean (SEM) 53 (4.2) v 57 (3.8)-APD; 62 (5.8) v 63 (5.6)-placebo). The lack of effect on radiological progression in the APD group indicates that focal erosive disease may either have progressed as the result of a non-osteoclast related mechanism, or that the intensity of bone resorption was too great to be inhibited by the doses of APD used. The biochemical response to APD presumably reflected inhibition of bone resorption at other sites, suggesting that further studies of the effects of bisphosphates on periarticular and systemic osteoporosis in rheumatoid arthritis may be of the interest.